Pretrial After the Enactment of Law Number 20 of 2025 on Criminal Procedure Code (KUHP) - Guntur Rambey (International Asia Of Law and Money Laundering (IAML), 2026)
The enactment of Law Number 20 of 2025 concerning the Indonesian Code of Criminal Procedure (KUHAP) brings fundamental changes to the institution of pretrial examination (praperadilan), which was previously regulated in a limited manner under Law Number 8 of 1981 and had long been criticized as a weak, formal-administrative mechanism for protecting human rights. This study aims, first, to analyze the regulation and expansion of the scope of praperadilan under the new KUHAP compared to the old one; and second, to examine the juridical implications of this institutional transformation for the protection of the constitutional rights of suspects, defendants, victims, and other interested parties within the integrated criminal justice system. This research employs a normative juridical method with a statutory and conceptual approach, examining primary legal materials in the form of both laws together with relevant secondary legal materials from prior studies. The findings indicate that the new KUHAP expands the object of praperadilan from three to six categories, broadens the scope of eligible applicants to include victims and reporters, and strengthens remedial mechanisms through the exclusionary rule principle. Nevertheless, this expansion also raises risks of abuse of rights through tactical delay as well as institutional implementation challenges that demand stronger implementing regulations, improved capacity of law enforcement officers, and consistent application of due process of law to ensure that the judicial control function of praperadilan operates effectively and fairly.